Viewpoint New Approaches to the 'Plague of Justinian'. Issue 1 (13th November 2021) - Sarris, Peter
Abstract: This viewpoint is meant as a contribution to debate over the nature and significance of the 'Justinianic Plague', which struck Western Eurasia between the sixth and eighth centuries ce, and the methodological challenges posed by attempting to reconcile historical evidence with that derived from the realm of the Natural Sciences. In recent years, major advances have been made in our genetic understanding of the Justinianic Plague. Yet growing scientific interest in the disease has coincided with a concerted effort amongst some historians to seek to downplay its historical importance. This article surveys our current state of historical and scientific understanding with respect to the sixth-century pandemic, responds to the recent attempts to argue that the disease had only a minimal impact on the societies that it struck, and considers how historians should respond to the burgeoning scientific evidence in order to take study of the plague forward. For co-operation between geneticists, environmental scientists, archaeologists and historians, it argues, offers the chance to transform our understanding of how, when and where the plague spread and to assess its impact across the Afro-Eurasian world as a whole, and not just on the Mediterranean, for which we have our best written sources.